2020
DOI: 10.1002/mus.27024
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19–associated Guillain‐Barré syndrome: The early pandemic experience

Abstract: Guillain-Barré syndrome (GBS) is an inflammatory polyradiculoneuropathy associated with numerous viral infections. Recently, there have been many case reports describing the association between coronavirus disease-2019 (COVID-19) and GBS, but much remains unknown about the strength of the association and the features of GBS in this setting. We reviewed 37 published cases of GBS associated with COVID-19 to summarize this information for clinicians and to determine whether a specific clinical or electrodiagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
245
2
26

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(279 citation statements)
references
References 63 publications
(67 reference statements)
6
245
2
26
Order By: Relevance
“…Acute motor and sensory axonal neuropathy and acute motor axonal neuropathy types were observed in 13.5% and 2.7% of cases. 4 In the present report, we discuss a case of axonal-type GBS associated with SARS-CoV-2 infection, where the patient was tested for various antiganglioside antibodies. Furthermore, we review the cases of SARS-CoV-2-infection-related GBS reported to date, in order to provide insight into the clinical characteristics and pathological mechanisms underlying the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Acute motor and sensory axonal neuropathy and acute motor axonal neuropathy types were observed in 13.5% and 2.7% of cases. 4 In the present report, we discuss a case of axonal-type GBS associated with SARS-CoV-2 infection, where the patient was tested for various antiganglioside antibodies. Furthermore, we review the cases of SARS-CoV-2-infection-related GBS reported to date, in order to provide insight into the clinical characteristics and pathological mechanisms underlying the disease.…”
Section: Introductionmentioning
confidence: 99%
“…( Lampe et al, 2020 ; Sedaghat and Karimi, 2020 ; Camdessanche et al, 2020 ) There might be a concern about thromboembolic complications of administration IVIg since there is a hypothesis of thrombotic susceptibility of COVID-19. ( Caress et al, 2020 ) But no adverse effects have been reported until the publication of this article.…”
Section: Discussionmentioning
confidence: 86%
“…The second SARS-CoV-2 PCR of nasopharyngeal swap was positive, so in this case, neuropathy possibly occurred during symptomatic infection with the SARS-CoV-2. In other reported cases of GBS associated with COVID-19, the nadir of neurologic symptoms was within 7 days of onset, sometimes 2–3 days and infrequently in the second week of neurologic illness ( Caress et al, 2020 ). Our patient was treated with IVIg, like almost all other reported GBS associated with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…77 However, it is also possible that GBS cases have been incorrectly attributed to critical illness neuromyopathy. 78 Miller Fisher syndrome. Miller Fisher syndrome is an acute peripheral neuropathy that develops after exposure to viral, bacterial, and fungal pathogens.…”
Section: Digestive System Manifestationsmentioning
confidence: 99%